Kontruksi Sosial Mahasiswa Umri Atas Kredibilitas Informasi Pinjaman Online Di Mobile Game - Nurrahmi; Jupendri; Fitria Mayasari (STAI Bumi Silampari, 2026)
The credibility of information is crucial for decision-making, as reliable information typically comes from clear sources, is supported by evidence, and is presented objectively. However, in entertainment media such as games, the line between information and advertising is often blurred, making it difficult for students to distinguish between credible and manipulative information. Online loan advertisements in mobile games frequently appear and influence students' mindsets and financial decisions. These advertisements encourage consumptive behavior due to low financial literacy and self-control. The purpose of this study was to determine and analyze how social construction affects the credibility of online loan information in mobile games. The research method used was a qualitative approach utilizing Social Construction Theory. The research subjects were students from the University of Muhammadiyah Riau. Data were collected through interviews and documentation. Then, the data were analyzed through data reduction, data presentation, verification, and conclusions. This study concludes that the phenomenon of online loan advertisements in mobile games is a result of cyclical and dynamic social construction, where reality is shaped not only by institutional actors but also by social relations between individuals within the student digital community.